Dynamic Response of WMoZrNiFe Energetic Structural Material Based on SHPB - Guiyan Pei; Zhe Peng; Xiaolu Bi; Qingjie Jiao; Rui Liu; Jianxin Nie (Metals)
Energetic structural materials (ESMs) are widely studied due to their high energy density, which enhances their potential in various industrial and engineering applications, such as in energy absorption systems, safety devices, and structural components that need to withstand dynamic loading. A high-strength WMoZrNiFe energetic structural material was prepared, and its mechanical properties and ignition behavior under dynamic loading were studied. Using the split-Hopkinson pressure bar (SHPB) experimental device, samples with different initial tilt angles of 0°, 30°, and 45° were dynamically loaded. The influence of the sample tilt angle on the ignition threshold was analyzed. The dynamic mechanical properties, failure modes, and ignition threshold based on the energy absorption of the WMoZrNiFe energetic structural material during the dynamic loading process were obtained. The results show that the material has a strain rate effect in the range of 1000 s−1~3000 s−1. The yield strength of the sample with a tilt angle of 0° increased from 1468 MPa to 1837 MPa, that of the sample with a tilt angle of 30° increased from 982 MPa to 1053 MPa, and that of the sample with an inclination angle of 45° increased from 420 MPa to 812 MPa. Through EDS elemental analysis, the ignition reaction mechanism of the WMoZrNiFe energetic structural material under dynamic compression was obtained. The violent reaction of the material occurred after the material fractured, and the active elements reacted with oxygen in the air.